2017
DOI: 10.1177/0009922817730344
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Behavioral Health Care in Pediatric Primary Care: A Quality Improvement Project

Abstract: The top 5 reasons for pediatric office visits in the United States today are behavioral health concerns. This article describes a colocated behavioral health and care coordination integration model in a pediatric primary care office to reduce barriers to behavioral health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Another recent study assessed how a single colocated behavioral health and care coordination integration model in a single urban pediatric primary care office was associated with changes in patient experience, provider experience, population health quality (eg, the Pediatric Symptom Checklist, PHQ‐9 Adolescent Depression Scale, Vanderbilt Assessment Scale), and medical expenditures. Results suggested that the intervention was associated with some measured improvements in population health quality and decreases in cost . However, the study was descriptive only; it did not report statistical significance nor did it include a comparison group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another recent study assessed how a single colocated behavioral health and care coordination integration model in a single urban pediatric primary care office was associated with changes in patient experience, provider experience, population health quality (eg, the Pediatric Symptom Checklist, PHQ‐9 Adolescent Depression Scale, Vanderbilt Assessment Scale), and medical expenditures. Results suggested that the intervention was associated with some measured improvements in population health quality and decreases in cost . However, the study was descriptive only; it did not report statistical significance nor did it include a comparison group.…”
Section: Discussionmentioning
confidence: 98%
“…Results suggested that the intervention was associated with some measured improvements in population health quality and decreases in cost. 65 However, the study was descriptive only; it did not report statistical significance nor did it include a comparison group. Our study serves as the first known study to assess the impact of a pediatric behavioral health integration model on health care utilization and cost using quasi-experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The care integration model with the most evidence—collaborative care—emphasizes active collaboration and communication among care team members in collaboration with the pediatric primary care provider. 4 Indeed, numerous trials of collaborative care have documented improvements in mental and physical health outcomes for chronic adult psychiatric disorders (eg, depression, anxiety, bipolar disorder). 13,14 Adolescents and young adults with BH diagnoses have low BH treatment rates largely attributed to lack of integration.…”
Section: Benefits and Challenges Of Integrated Pediatric Health Carementioning
confidence: 99%
“…[1][2][3] BH concerns are among the top reasons families seek care in primary care medical homes. 4 Care integration offers several advantages, including increasing access to BH care for children in their medical home, 5 allowing families to work with a familiar provider, and providing practical, user-friendly materials to address child and caregiver BH. 6 Integration may also promote continuity of care by increasing the capacity of the indigenous workforce to engage families and deliver services, and reduce the risks for adverse family outcomes (eg, threats to child safety, need for more intensive services or placement).…”
mentioning
confidence: 99%
“…Research shows that approximately 90% of children visit a pediatrician in any given year 2 . Pediatricians serve at the front‐line in identifying and treating behavioral health concerns in young patients 2‐5 . Most children with behavioral, developmental, and emotional problems are spotted first by pediatricians 6 .…”
Section: Introductionmentioning
confidence: 99%